Hughes electrical & electronic technology - Hughes, Edward, 1888-; Hiley, John; Brown, Keith, 1962-; Smith, Ian McKenzie (Always learning., 2016)
"All engineers need to understand the fundamental principles of electrical and electronic technology. This best-selling text provides a clear and accessible introduction to the area, with balanced coverage of electrical, electronic, and power engineering."--Back cover.